The efficiency of developing coordination skills in figure skaters during the initial training phase - Babushkina L. E.; Matveenko D. I.; Tuzova E. N.; Mirzoev V. I. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to enhancing the coordination skills of young skaters aged 6-8 years during the initial training phase to enhance their technical proficiency.